Presentation: Memories of Pain and Signs of Hope (II) - Caram Padilla, María José (2003)
Continuing with the theme of violence and hope in our societies, it presents interesting works on the role of mental health workshops in the southern Andes, domestic violence and child abuse, as well as religious violence. It includes an article on the mystique of the saint of the poor and of the Spanish poets: Saint John of the Cross, co-founder of the Order of the Discalced Carmelites with Saint Teresa of Jesus. Latin America continues to walk a history of pain, of struggles, but also of hope. Poverty and violence are realities that occur without interruption over the decades and, why not say it?, over the centuries. However, always, and despite everything, there was a place for poetry, song and dance.